2011
DOI: 10.1007/s10531-011-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungal communities in woody perennials of three tropical forest types of the Western Ghats, southern India

Abstract: Fungal endophytes of tropical trees are expected to be exceptionally species rich as a consequence of high tree diversity in the tropics and the purported host restriction among the endophytes. Based on this premise, endophytes have been regarded as a focal group for estimating fungal numbers because their possible hyperdiverse nature would reflect significantly global fungal diversity. We present our consolidated ten-year work on 75 dicotyledonous tree hosts belonging to 33 families and growing in three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 61 publications
7
52
0
Order By: Relevance
“…Dattaraja, H.S. Suresh & R. Sukumar, unpublished data -see Suryanarayanan et al 2011a) supports a higher phellophyte diversity as has been observed for endophytic fungi (Arnold et al 2000).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Dattaraja, H.S. Suresh & R. Sukumar, unpublished data -see Suryanarayanan et al 2011a) supports a higher phellophyte diversity as has been observed for endophytic fungi (Arnold et al 2000).…”
Section: Discussionsupporting
confidence: 64%
“…Among the endophytes, those that infect leaves have been studied for their diversity (eg. Suryanarayanan et al 2011a) and technological potential (Suryanarayanan et al 2009a, Verma et al 2009, Suryanarayanan et al 2012. However, there are very few studies on endophytes which reside in the outer barks of trees.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Chagnon et al (2016) conclude that endolichenic fungi are not strictly host specific and behave as generalists when compared with endophytes. Some endophytic fungi such as Colletotrichum, Pestalotiopsis, Phomopsis and Xylaria (Suryanarayanan et al 2011; Govinda Rajulu et al 2013; Sudhakara Reddy et al 2016) also exhibit loose host affiliation and infect taxonomically unrelated plants. Different lichen species from different habitats have to be screened to determine the prevalence of such cosmopolitan endolichenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutically important secondary metabolites-producing endophytes, compatible with in vitro cultures offer special advantages that include cost-effective large scale production of the metabolites in industrial laboratory settings. In this regard, endophytes from marine habitats appear to be unique since many of them produce different novel (Bugni and Ireland 2004;Jones et al 2008;Raghukumar 2008;Schulz et al 2008;Kjer et al 2010;Suryanarayanan et al 2011;Flewelling et al 2013). Nearly 30% of the novel metabolites produced by marine-derived fungi are from fungi associated with marine algae (Bugni and Ireland 2004); some of these fungi produce metabolites having hitherto unknown carbon frameworks (Kjer et al 2010) .…”
Section: Discussionmentioning
confidence: 99%
“…All these isolates were maintained in Vivekananda Institute of Tropical Mycology (VINSTROM), Ramakrishna Mission Vidyapith, Chennai. The endophytes were isolated by surface sterilising the plant tissues with ethanol and sodium hypochlorite (Suryanarayanan et al 2010(Suryanarayanan et al , 2011Murali et al 2013 …”
Section: Endophyte Isolates Usedmentioning
confidence: 99%